Designing Weight Training Programs Based on Basic Principles - Giechaskiel, Barouch (Journal of Sports Research, 2020)
A weight (resistance) training program includes training variables, such as exercises, sets, repetitions and training frequency. A training plan describes how the variables should be modified over time. In order to be effective, both training programs and plans should be based on some basic principles, applicable to all trainees. Based on the literature review, the most important and well supported is the principle of progressive overload, which states that the stimulus should be gradually increasing over time. The principle of specificity states that the training adaptations are specific to the stimulus applied, while the principle of variation (and periodization) states that the stimulus should change (within the specificity limits) to remain challenging. Although they are not necessary to increase performance, there is evidence supporting higher improvements. The principle of individuality states that the stimulus should be adjusted based on the individual’s needs. Even though overlooked, limited data indicate that it may be more important than specificity and variation. This paper discusses the basic principles, the criticism against them, and how they should be applied when designing resistance training programs.